Intra rater reliability of Y balance test in medical students - Muhammad Mustafa Gul; Sidrah Shabbir; Muhammad Burhan; Muhammad Mahmood Alam; Muhammad Waseem Akhtar; Muhammad Shahbaz (Journal of the Pakistan Medical Association, 2025)
The cross-sectional study was planned to assess the Y-balance test's intra-rater reliability among a sample of 59 medical students. The subjects took six trials under supervision, and the reliability of the results improved, with intra-class correlation values >0.75, indicating high reliability. Though the study had a cross-sectional design, it provided insightful data for focussed assessment. The Y-balance test was found to be an easy and reliable technique for evaluating dynamic balance. Key Words: Balance, Muscle strength, Reliability, Intra-rater reliability, Y-balance test.